2006
DOI: 10.2109/jcersj.114.220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AlN Addition on the Consolidation of SiC with Stacking-Disordered Structure

Abstract: Consolidation of SiC powder with stacking disordered structure was accelerated by milling with the AlN as the additive. SiC powders without the additive were sintered at 1900c C to a density of 99ಚ. The grain size of the sintered material was approximately 500 nm. On the other hand, with AlN as additive, the sintering temperature to reach a density of 98ಚ was reduced to 1700c C by the addition of 1.0 molಚ AlN. The grain size of this material was approximately 50 nm. The effect of AlN addition on SiC sintering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The grain growth and sintering is usually enhanced with the fine powder with many crystalline defects. As one of example for sintering and grain growth of ceramics, the role of disorder-order transformation in consolidation of SiC was reported by Ohyanagi et al [10][11][12][13]. They investigated the ordering of stacking-disordered SiC prepared from the elements by high energy ball milling during sintering process [12].…”
Section: Resultsmentioning
confidence: 99%
“…The grain growth and sintering is usually enhanced with the fine powder with many crystalline defects. As one of example for sintering and grain growth of ceramics, the role of disorder-order transformation in consolidation of SiC was reported by Ohyanagi et al [10][11][12][13]. They investigated the ordering of stacking-disordered SiC prepared from the elements by high energy ball milling during sintering process [12].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that spark plasma sintering (SPS) can shorten the sintering time and lower the sintering temperature of AlN–SiC composites with Y 2 O 3 as sintering additive 19 . Shirai et al 20 carried out low‐temperature sintering of SiC nanopowder with a small amount of AlN using SPS. We have also reported that the SPS can provide dense AlN–SiC composites without sintering additives, which have a fine microstructure with smaller grains but comprise several solid solution phases 21 .…”
Section: Introductionmentioning
confidence: 93%